Identification of key extracellular proteins as the potential biomarkers in thyroid eye disease - Shasha He; Han Nie; Xiangbao Yin; Zhiwei Zhong (PLoS ONE, 2025)
Background Thyroid eye disease (TED) is one of the most common autoimmune orbital diseases in adults. The early diagnosis and effective treatment of TED is a worldwide problem. Extracellular proteins may act as indicators in bodily fluids. Our research sought to identify the roles of extracellular proteins and possible biomarkers in TED using a bioinformatics study. Methods Data from Gene Expression Omnibus (GEO) were acquired to create the TED expression profiles. The annotation database screened extracellular proteins with differentially expressed genes (EP-DEGs). To investigate both the function and the route of EP-DEGs, GO and KEGG were utilized. Hub genes and protein-protein interaction (PPI) networks among EP-DEGs were discovered. Key EP-DEGs’ diagnostic potency was assessed using the receiver operating characteristic (ROC) curve. Results 102 EP-DEGs underwent screening. The extracellular matrix, which contains collagen, the receptor-ligand activity, the interaction between cytokines and their receptors, and the complement and coagulation cascades route, were all enhanced in EP-DEGs. The EP-DEG PPI network contained 233 edges and 78 nodes. We discovered 21 extracellular proteins that interacted with EGFR in addition to 3 major extracellular proteins, EGFR, CD44, and CXCL8, all of which had significant values of AUC (> 0.7). Conclusions In conclusion, EGFR, CD44, and CXCL8 may be the potential biomarker in the TED. this research gives us a theoretical foundation for understanding how TED pathogenesis occurs.